Improvement of the therapeutic treatment of inflammatory bowel diseases following rectal administration of mesalazine-loaded chitosan microparticles vs Asamax®. (15th May 2019) - Palma, Ernesto; Costa, Nicola; Molinaro, Roberto; Francardi, Marco; Paolino, Donatella; Cosco, Donato; Fresta, Massimo
Graphical abstract: Highlights: Mesalazine was efficiently encapsulated in chitosan microparticles. The microsystems are characterized by significant bio-adhesion. The formulation promoted significant anti-inflammatory activity. Microencapsulated mesalazine may be used for the treatment of IBDs. Abstract: The development of innovative strategies for the efficacious treatment of inflammatory bowel diseases (IBD) still remains a goal for pharmaceutical research. Targeting the lower section of the intestine is the main aim of therapy because it is the compartment primarily affected by IBDs. Mesalazine was microencapsulated in chitosan particles in order to modulate its unfavorable pharmacokinetic profile exploiting the bioadhesive feature of the polysaccharide and increase the anti-inflammatory effect of the drug following its rectal administration in an in vivo model of induced IBD. The chitosan microparticles (1–4 μm mean size) allowed efficient retention of the mesalazine and a prolonged drug release lasting up to 48 h. In vitro and in vivo experiments confirmed the significant mucoadhesion feature of the formulation by means of mucin assay and CLSM experiments and demonstrated its therapeutic efficacy at a drug concentration 2-fold lower than the commercial formulation Asamax ® (13 mg/kg vs 26 mg/kg).